Potential Pathways Involved in Elaidic Acid Induced Atherosclerosis in Human Umbilical Vein Endothelial Cells - Huahong Yu; Xiangmei Li; Zhongshang Liang; Bin Qiu; Siguang Li; Ting Luo; Jing Li; Hongyan Li; Zeyuan Deng (Journal of Chemistry)
Researches have demonstrated that trans-fatty acids are related to the progression of atherosclerosis, but the underlying mechanism is not clear till now. In the presented study, two-dimensional electrophoresis based proteomics was used to discover the role of elaidic acid in atherosclerosis. In human umbilical vein endothelial cells (HUVEC), twenty-two and twenty-three differentially expressed proteins were identified in low (50 μmol/L) and high (400 μmol/L) concentration elaidic acid simulated groups, respectively, comparing with the control group. The expressions of some selected proteins (PSME3, XRCC5, GSTP1, and GSTO1) were validated by qRT-PCR analysis. Western blotting analysis further confirmed that elaidic acid downregulated the expression of PSME3 and XRCC5. Moreover, P53, the downstream protein of PSME3, was further investigated. Results demonstrated that a variety of proteins, many of which were related to oxidative stress, apoptosis, and DNA damage, were involved in the elaidic acid induced atherosclerosis. Furthermore, P53 was demonstrated to regulate the atherosclerosis through cell cycle arrest and apoptosis pathway.